FENOMENA PROSTITUSI DI PANTAI SAMAS BANTUL YOGYAKARTA - Vivi Ambarwati * (Pendidikan Sosiologi FIS UNY, 2012)
The phenomenon of prostitution is usually often appear in tourist areas. Prostitution has also appeared in the district of Bantul Samas Beach Yogyakarta despite local laws that prohibit prostitution. This study aims to: 1). Describe the factors that cause the existence of prostitution in Samas Beach, 2). Describe the community and local government efforts in dealing with prostitution in Samas Beach.This study used descriptive qualitative method of analysis. Informants in this study were CSWs (Commercial Sex Workers) Samas Beach, citizens around and Satpol PP Bantul regency. The research subject was taken by snowball sampling technique. The number of prostitutes in Samas Beach is currently under number 10, so that sampled quite four informants sex workers because of data and information obtained is adequate. The process of data collection is done with the interview, non-participatory observation, field recording and documentation. Researchers itself is a qualitative research instrument, but also coupled with the guidance interview and observation guidelines. Validity of data using data triangulation technique. Techniques in data analysis is the technique of Miles and Huberman interactive analysis with 4 stages, namely: data collection, data reduction, data presentation and conclusion.The results showed that: 1). The factors causing the existence of prostitution inSamas Beach is divided into two: internal and external factors. Internal factors causing the existence of prostitution in Samas Beach is derived from the self-sex workers Samas Beach is: do not have other life skills, frustration and trauma and sexual needs. While the external factors causing the existence of prostitution in Samas Beach namely: economic factors, call a friend, the narrowness of employment, abuse and misuse of bus terminal facilities stalls shacks wild, 2). Grassroots efforts and local governments in dealing with prostitution in Samas Beach is: social control of routine patrolling and monitoring, implementing regulations Bantul district no. 5 year 2007 on the prohibition of prostitution, conducting raids sex workers, providing skills training, lowcost health care through mobile health center and routine supervision of the police station Sanden and police station Bantul.Key words: the phenomenon of prostitution, sex workers and surrounding communities